2011
DOI: 10.1111/j.1540-6237.2011.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contact Hypothesis and Attitudes Toward Latinos in the United States

Abstract: Objectives. Although the contact hypothesis occupies an important place in the study of intergroup relations, several important questions remain understudied. We contribute to the literature by examining the associations between multiple aspects of contact with Latinos and several types of attitudes toward U.S. Latinos, including attitudes toward immigration restrictions. Methods. We use OLS and logistic regression techniques to analyze the opinions of Anglo (non-Hispanic white) and African-American respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 58 publications
(78 reference statements)
1
69
0
3
Order By: Relevance
“…While contact theory developed from experimental research, survey research supports its generalizability (Pettigrew 1998; Pettigrew and Tropp 2011). In surveys, respondents with cross-racial friendships report lower levels of prejudice (Emerson, Kimbro, and Yancey 2002; Ellison, Shin, and Leal 2011), as do those living in more racially and ethnically integrated neighborhoods (Oliver and Wong 2003). However, while the effect of living in a more diverse neighborhood reduces prejudice, living in a more diverse metropolitan area increases it (Fosset and Kiecolt 1989; Quillian 1996; Taylor 1998).…”
Section: Theories Of Prejudice: the Group Threat And Contact Hypothesesmentioning
confidence: 99%
“…While contact theory developed from experimental research, survey research supports its generalizability (Pettigrew 1998; Pettigrew and Tropp 2011). In surveys, respondents with cross-racial friendships report lower levels of prejudice (Emerson, Kimbro, and Yancey 2002; Ellison, Shin, and Leal 2011), as do those living in more racially and ethnically integrated neighborhoods (Oliver and Wong 2003). However, while the effect of living in a more diverse neighborhood reduces prejudice, living in a more diverse metropolitan area increases it (Fosset and Kiecolt 1989; Quillian 1996; Taylor 1998).…”
Section: Theories Of Prejudice: the Group Threat And Contact Hypothesesmentioning
confidence: 99%
“…A meta-analysis of 551 studies conducted in 38 different countries found evidence for a significant negative effect of intergroup contact on social prejudice in over 90 per cent of the studies sampled (Pettigrew and Tropp 2008). Further, focusing on immigration, Schneider (2008) and Ellison et al (2011) each find that intergroup contact or personal relationships with immigrants can increase the acceptance of immigrants among natives, with Schneider (2008: 60) noting that people who experienced intergroup contact feel 'less threatened by immigrants than others'.…”
Section: Immigration Diversity and Attitudes: Existing Literaturementioning
confidence: 99%
“…Our objective is to assess the degree to which people encounter groups other than their own , as part of their routine activities. Racial/ethnic and income segregation are important, in part, because contact among social groups may have important effects on a person’s assumptions about, and attitudes toward, other social groups and how they live (Chaskin and Joseph 2011; DiPrete et al 2011; Ellison et al 2011; Pettigrew 2008; Rocha and Espino 2010). These assumptions and attitudes may be important for social solidarity, political behavior, and many other aspects of urban life.…”
Section: Introductionmentioning
confidence: 99%
“…The intergroup contact literature suggests that contact between social groups may decrease prejudice and negative assumptions particularly assumptions—that advantaged groups hold toward out-groups (Ellison et al 2011; Lee et al 2004; Pettigrew and Tropp 2008; Tropp and Pettigrew 2005). This literature has traditionally focused on white prejudice toward racial and ethnic minority groups.…”
Section: Introductionmentioning
confidence: 99%